지하철 환승역의 길찾기 스트레스 측정에 관한 실험 연구 - 전효정; Jeon Hyojung; 정진우; Jung Jinwoo (기초조형학연구, 2020)
본 연구의 목적은 사소하다고 생각되어질 수 있는 길찾기의 실패가 사용자의 스트레스에 영향을 미치는가에 대하여 알아보는 것이다. 따라서 지하철 환승역에서 길을 헤매게 만드는 환경요인인 사인의 가림, 위치, 각도 등을 독립변수로 설정해 길찾기 결과에 영향을 미치는지, 또한 그로 인한 길찾기 결과가 사용자의 스트레스에 영향을 미치는지 알아보았다. 실험은 두 개의 가상 공간에서 이루어졌다. 대조군은 사인이 모두 사람이 보는 방향에 있으며, 적정거리마다 사인이 배치되었다. 실험군은 사인이 기둥 등과 같은 다른 사물에 의해 가려져 있거나, 보는 각도와 방향에 위치하지 않아 사인을 단번에 찾을 수 없고, 적정거리마다 사인이 배치되어 있지 않은 구간이 존재하는 공간이다. 이 두 가상현실공간에서 제한 시간 내에 지정된 목적지를 찾는 실험을 진행하고 사후 설문지 작성을 통해 길찾기 결과에 따른 스트레스 정도를 조사하였다. 연구 결과, 두 개의 실험 공간에서 제한 시간 내에 실험을 성공한 횟수와 도착지점까지 소요된 시간, 스트레스 반응과 관련된 긍정 및 부정 감정 어휘, 그리고 실험의 난이도에서 유의한 차이가 드러났다. 따라서 본 연구를 통해 환경요인이 길찾기 결과와 스트레스에 영향을 미치며, 그 길찾기 결과는 사용자의 스트레스에 영향을 미친다는 사실이 발견되었다. 본 연구에서의 길찾기 실패는 아주 단순하고 매우 미미한 것임에도 불구하고 피험자들 대부분은 자가진단을 통해 스트레스 반응을 나타냈다. 이 결과는 일상적이지 않은 환경에서의 상대적으로 큰 길찾기 실수는 본 연구에서 측정된 스트레스 정도보다 더 크게 나타날 수 있다는 것을 의미한다. 그러므로 길찾기 문제는 사용자들이 공간을 사용하는 기능적인 관점에서 단순하게 접근해야 할 것이 아니라 사용자의 감정적 입장에서 폭넓게 확장되어 접근되어야 한다. The purpose of this study is to investigate whether the failure of wayfinding which can be considered minor, affects the user's stress. The researcher set up the sign’s obscurity, location, angle, and so on, which are environmental factors that make people wander the subway transit station, as an independent variable to determine whether it affects the wayfinding results and whether the wayfinding results affect the user's stress. The experiment was conducted in two virtual spaces. In the control group, all the signs were in the direction of human viewing, and signs were placed at appropriate distances. The experimental group is a space in which the signs are hidden by another object such as pillars or are not located at the viewing angle and direction so that the signs cannot be found at once, and there is a section in which the sign is not arranged at a proper distance. In these two virtual reality spaces, the experiment was conducted to find the designated destination within the time limit, and the post questionnaire was used to investigate the stress according to the wayfinding results. The experiment results showed that there are significant differences in the number of successful experiments within the time limit, the time taken to the arrival point, the positive and negative emotional vocabulary related to the stress response, and the difficulty of the experiment. Therefore, this study found that environmental factors influenced the wayfinding results and stress, and the wayfinding results influenced the stress of the user. Although the wayfinding failure in this study was very simple and insignificant, most of the subjects showed a stress response through the selfdiagnosis. The results indicate that wayfinding mistakes in unusual environments may be greater than the stress levels measured in this study. Therefore, the wayfinding problem should not be approached simply from the functional point of view of users using space, but from the user's emotional point of view as well.